Ovarian Reserve In Infertile Women with and without Endometriosis Measured with Anti Müllerian Hormone - Harharah, Naivah (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To compare serum Anti Müllerian Hormone (AMH) levels in infertile women with and without endometriosis, and to determine the mean levels of serum AMH in every stage of endometriosis. Method: We performed a cross-sectional study. Sixty-eight subjects who have undergone laparoscopy and fulfilled both inclusion and exclusion criteria are recruited consecutively. They are divided into two groups, namely group with endometriosis and without endometriosis. Blood samples are taken from each subject before laparoscopy, where serum AMH levels are then measured. The difference in mean levels of each group are tested with Mann-Whitney test. Result: The mean levels of serum AMH were significantly lower in the endometriosis group than those in the group without endometriosis (2.30 1.8 ng/ml vs 3.75 2.13 ng/ml; p=0.005). Using Kruskal-Wallis test, it was found that there was a statistically significant difference among endometriosis groups based on the severity of endometriosis. There was no significant difference in the mean serum AMH levels between the minimal-mild endometriosis group and without endometriosis group (p=0.34), but the mean levels of serum AMH were significantly lower in the moderate-severe endometriosis compare to the group without endometriosis (p